The Influence of Social Media Marketing and Brand Awareness on Purchase Decisions of Fashion Products among Generation Z on TikTok Shop - Pipit Purnamasari; Muhammad Nur Abdi (International Journal of Business and Quality Research, 2025)
Recently, TikTok has experienced rapid growth as an entertainment platform. In addition to its entertainment features, the platform also provides an e-commerce function that enables real-time transactions and promotions. TikTok Shop has become one of the primary shopping platforms for Generation Z, particularly for fashion products. This study aims to further explore this phenomenon by examining how Brand Awareness is influenced by Social Media Marketing and to what extent both factors affect consumers’ purchase decisions on TikTok Shop. A quantitative approach was employed using regression analysis to address these objectives, involving 140 respondents, the majority of whom were active TikTok Shop users. The results reveal a clear pattern in which Brand Awareness is significantly influenced by Social Media Marketing. Furthermore, these variables were found to affect purchase decisions both independently and simultaneously. The findings highlight the importance of TikTok’s features in the context of digital marketing, such as short videos, user engagement, and influencer endorsements, which play a crucial role in enhancing brand awareness. Ultimately, in addition to increasing Brand Awareness, these components also motivate consumers to make purchase decisions